Meeting the challenges of flexible work designs: effects of an intervention based on self-regulation on detachment, well-being, and work-family conflict - Althammer, Sarah Elena; Wöhrmann, Anne Marit; Michel, Alexandra (Journal of happiness studies, 2025)
Self-regulation is important for coping with demands of flexible work designs (FWD) such as telework, remote work, or flextime. This article evaluates a web-based intervention based on self-regulation models to enable workers meet challenges of FWD and thus improve recovery, work-life balance, and well-being. Over six weeks, participants learnt self-regulation strategies to detach from work, segment work and private life, and organize their workday. In a randomized controlled trial, participants were assigned to an intervention group or a waitlist control group. Study participants rated their levels of self-regulation, psychological detachment, strain-based work-family conflict (WFC), and affective, cognitive and work-related well-being (indicated by positive affect, stress, and work engagement) before and after the intervention, and at a four-week and six-month follow-up. The final sample after the training included 358 participants (intervention group: n = 147; control group: n = 211). As expected, covariance analyses revealed that the intervention improved positive affect and work engagement, and that it reduced stress and strain-based WFC. Moreover, we found positive effects on psychological detachment for participants with low baseline levels of psychological detachment. Self-regulation mediated intervention effects on positive affect and work engagement. Effects hold at four-week and six-month follow-ups, except for work engagement. Overall, findings indicate that the intervention is an effective tool for promoting self-regulation and enabling workers to achieve their goals regarding recovery, work-life balance, and well-being.